2020
DOI: 10.3389/fphar.2020.587663
|View full text |Cite
|
Sign up to set email alerts
|

Bu-Shen-Huo-Xue Decoction Ameliorates Diabetic Nephropathy by Inhibiting Rac1/PAK1/p38MAPK Signaling Pathway in High-Fat Diet/Streptozotocin-Induced Diabetic Mice

Abstract: Diabetic nephropathy (DN), a leading cause of end-stage renal disease, is associated with high morbidity and mortality rates worldwide and the development of new drugs to treat DN is urgently required. Bu-Shen-Huo-Xue (BSHX) decoction is a traditional Chinese herbal formula, made according to traditional Chinese medicine (TCM) theory, and has been used clinically to treat DN. In the present study, we established a high-fat diet/streptozotocin-induced diabetic mouse model and treated the mice with BSHX decoctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…There is a significant body of literature demonstrating an increased interest in herbal products, driven by the recognition that multi-ingredient formulations offer enhanced efficacy for managing complex diseases [ 38 , 39 ]. Traditional Chinese Medicine has shown remarkable effectiveness in alleviating clinical symptoms, slowing the progression of DKD, enhancing renal function, and improving patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…There is a significant body of literature demonstrating an increased interest in herbal products, driven by the recognition that multi-ingredient formulations offer enhanced efficacy for managing complex diseases [ 38 , 39 ]. Traditional Chinese Medicine has shown remarkable effectiveness in alleviating clinical symptoms, slowing the progression of DKD, enhancing renal function, and improving patients' quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products or traditional Chinese medicines have been long used in patients and considered an alternative therapeutic strategy for prevention and treatment of glomerular-associated diseases including MN ( Feng et al, 2020 ), glomerulonephritis ( Gianassi et al, 2019 ; Wang et al, 2021 ), diabetes ( Chen et al, 2020b ; Wang et al, 2020b ; Fang et al, 2021 ; Su et al, 2021 ; He et al, 2022 ), and diabetic nephropathy ( Li et al, 2020a ; Yang et al, 2020 ; Wang, 2021 ; Xuan et al, 2021 ; Yang and Wu, 2021 ; Zhou et al, 2021 ; Liu et al, 2022 ). Earlier finding have demonstrated that a 77-year-old woman with IMN was treated by Astragalus membranaceus and achieved clinical remission without using immunosuppressive therapy ( Ahmed et al, 2007 ).…”
Section: Treatment Of Membranous Nephropathymentioning
confidence: 99%
“…Bu-Shen-Huo-Xue Decoction upregulates the podocyte markers nephrin and podocin in high-fat diet/STZ-induced diabetic mice and downregulates mesenchymal markers. α-SMA and fibroblast-specific protein 1 are expressed to improve renal function and inhibit podocyte EMT ( Wang et al, 2020 ). Rhodiola can increase the expression levels of nephrin and podocin and protect podocytes by regulating SIRT1/PGC-1α-mediated mitochondrial bioactivity and inhibiting the β-catenin signaling pathway ( Huang et al, 2019 ; Xue et al, 2019 ).…”
Section: Protective Effects Of Traditional Chinese Medicine and Activ...mentioning
confidence: 99%